2022
DOI: 10.1002/macp.202200248
|View full text |Cite
|
Sign up to set email alerts
|

Tailor‐Made Vinylogous Urethane Vitrimers Based on Binary and Ternary Block and Random Copolymers: An Approach toward Reprocessable Materials

Abstract: Vitrimers are promising reprocessable materials. To tune their properties, microphase separated block copolymers as backbones play an essential role in the thermal and mechanical properties of the resulting nanostructured networks. In this study, various narrow disperse di-and triblock copolymers containing a hydroxyethyl methacrylate block and, for comparison, random copolymers of the same comonomers are synthesized in a controlled manner by photoiniferter reversible addition-fragmentation chain transfer poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…According to the literature, the acetoacetylation of various alcohols as monomers for vinylogous urethane vitrimers is carried out in organic, high-boiling solvents like xylene or dimethylformamide. In times of increasing environmental pollution and the exploitation of fossil resources, it is desirable to use renewable raw materials and explore the expendability of (toxic) organic solvents. The acetoacetylation of several alcohols likewise takes place without using an additional organic solvent, only with the acetoacetylation agent, utilizing the same reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, the acetoacetylation of various alcohols as monomers for vinylogous urethane vitrimers is carried out in organic, high-boiling solvents like xylene or dimethylformamide. In times of increasing environmental pollution and the exploitation of fossil resources, it is desirable to use renewable raw materials and explore the expendability of (toxic) organic solvents. The acetoacetylation of several alcohols likewise takes place without using an additional organic solvent, only with the acetoacetylation agent, utilizing the same reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Similar conclusions were drawn in later works, in which significantly increased material properties were observed for phase-separated di-or triblock vitrimers as compared to the random polymers. 198,199 The increased creep resistance and slower bond exchange (i.e., higher activation energy) were mainly attributed to hindered polymer strand diffusion as a result of the phase separation. In other work by Clarke and coworkers, they even pushed the limits of phase separation in dynamic block copolymers to construct crosslinked tri-block copolymers that were able to self-assemble into interlinked, hexagonally packed cylinder nanostructures, limiting inter-cylinder bond exchange.…”
Section: Dynamically Crosslinked Block Copolymersmentioning
confidence: 99%
“…Similar conclusions were drawn in later works, in which significantly increased material properties were observed for phase-separated di- or triblock vitrimers as compared to the random polymers. 198,199 The increased creep resistance and slower bond exchange ( i.e. , higher activation energy) were mainly attributed to hindered polymer strand diffusion as a result of the phase separation.…”
Section: Covalent Adaptable Network (Cans)mentioning
confidence: 99%
“…Specifically, BCP vitrimers are a rising class of materials that incorporate dynamic covalent crosslinks into one of the BCP components, enabling derived polymers to have both thermoset-like material properties and thermoplastic-like processability. While several works have demonstrated that the impact of incorporating dynamic groups on the BCP nanostructure is dependent on the crosslinking chemistry, [94][95][96][97] the exact role of dynamic chemistry in controlling the BCP nanostructure and assembly dynamics remains not clear. [71][72][73][74] Furthermore, many studies on controlling BCP morphologies through reactions are limited to synthetic polymers derived from petroleum feedstocks.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%